Tajalliyât Sufistik Dialektika Nilai-Nilai Religius-Humanistik - Husni Hidayat (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
In the Sufi dimension, a tariqa is considered a madrasa (school) which leads a mutasawwif to purify the darkness of the heart from seven passions, namely ammârah bi al-sû’, lawwâmah, mulhamah, mutma’innah, râdiyah, and mardiyah. These seven lusts should be controlled and merged because they can cover humans from their nature. Under the guidance of the trustee murshid, the mutasawwifs are called and encouraged to reform themselves without seeing the disgrace of other people. However, such a process would not alienate the students from their social life and daily activities as the common people. Therefore, after two initial phases, namely takhallî and tahallî, a Sufi will reach his or her ultimate phase, i.e., tajallî. For the Sufis, the highest tajalli God is the Prophet. This is because he was the first creature of God and the complete man (al-insân al-kâmil). Muhammad is not a mere man, but he is a manifestation of God’s emanation.